Navigating Closed Doors: Systematic Barriers to Healthcare Access and Adolescent Resilience in the Context of Unintended Pregnancy in Makassar, Indonesia - Ruqaiyah Ruqaiyah (International Journal of Health and Social Behavior, 2026)
This study examines the experience of access to health services and resilience strategies in adolescents with unplanned pregnancies in Makassar, Indonesia. Access to quality reproductive health services is important for adolescents' well-being, but they often face systemic barriers that affect access to health services and outcomes. The study used an Interpretative Phenomenological Analysis (IPA) approach on seventeen adolescent girls aged 15–19 years who had an unplanned pregnancy between June–November 2023. Data were collected through in-depth semi-structured interviews, recorded, verbatim transcribed, and analyzed by a six-stage science process. Two main themes were found: Navigating Closed Doors: Systematic Barriers to Care and Finding Light in Darkness: Resilience and Agency. Participants faced a variety of layered barriers, including a lack of information about health services and rights, geographical and economic constraints, age-based discrimination, parental notification obligations, fear of legal consequences especially related to abortion, family control over decisions, and limitations in adolescent-friendly services. Nonetheless, adolescents show resilience through seeking strategic help, resistance to pressure, spiritual and religious coping, peer support, gradual acceptance of maternal identity, educational sustainability, and positive meaningfulness of difficult experiences. These findings point to the need for a transformation of the health system that not only improves attitudes of health workers, but also addresses structural barriers such as confidentiality, age discrimination, and service availability, while strengthening agency and adolescent coping strategies.